Analysis of the diet, weight-loss behavior, and nutritional knowledge of athletes and coaches in weightclass sports: influence of a coach's nutritional knowledge on athletes - Jun-Young Sung; Jung-Hoon Lee; Kyu-Lim Lee (Taylor & Francis Group, 2024)
Background This study was conducted to investigate the nutritional knowledge of elite athletes undergoing weight loss and to identify differences in weight-loss strategies according to nutritional knowledge.Methods The participants included 22 coaches and 88 elite athletes registered under the same affiliation. The survey involved translating the General Nutrition Knowledge Questionnaire (GNKQ), and interviews were used to confirm the diet and weight loss patterns of the athletes. The coaches and athletes were divided into high-rank (12 coaches and 57 athletes) and low-rank (10 coaches and 31 athletes) groups based on GNKQ scores. Paired t-tests, correlation analysis, and logistic regression analysis were performed.Results GNKQ results showed significant differences between high-ranking and low-ranking coaches (p < 0.001). Furthermore, a significant difference in nutrition knowledge scores was also noticed between athletes with high-ranking and low-ranking coaches (p < 0.001). A strong correlation was observed between the GNKQ scores of coaches and athletes (r = 0.369; p < 0.001). The nutritional knowledge of coaches was also correlated with weight-loss strategies (weight loss attempt frequency; r = -0.235; p = 0.027; weight loss duration; r = -0.268; p = 0.012). Additionally, differences were observed in the intake of all nutrients (carbohydrates, proteins, and fat) in the diets of athletes (p < 0.001).Conclusion Our study suggests that the nutritional knowledge of coaches indirectly affects athletes. Coaches have significant influence over athletes and possess experience with diet and weight-loss patterns. This insight should be effectively utilized to enhance the training and performance of athletes and coaches.